Glass-ceramics produced by vitrification of coal fly ash - Biljana Angjusheva, Emilija Fidancevska (My University, 2021)
Glass-ceramics based on CAS (CaO-Al2O3-SiO2) system was produced by controlled crystallization of vitrifi ed fl y ash. Fly ash was pre-treated by magnetic separation and nonmagnetic part of fl y ash (NFA) was used. Maximal crystallization of parent glass occurs in the temperature region from 900 oC to 1160 oC. Glass-ceramics was produced by consolidation of parent glass i.e. pressing (45 MPa) and sintering at 950, 1000, 1050 and 1100 oC, and aluminum silicate (anorthite). The obtained glass-ceramics could be potentially used in construction applications.
Keywords: coal fl y ash, parent glass, quenching, vitrifi cation, glass-ceramics